PSVII-13 Mineral feeder design impacts frequency of use in grazing beef cattle. (30th November 2020) - Crites, Benjamin; Boeglin, Michaela; Heath, Jaycie; Vanzant, Eric; Roy, Nicholas; Stamm, Clay; Sears, Brandon; Coffey, David; Campbell, Matthew; Musen, Steven; Barnes, Jessica; Williams, Victor; et al.
Abstract: Trace minerals are essential for many biological and metabolic processes and often supplemented ad libitum to grazing beef cattle. However, research has shown large variations in individual intakes. The objective of this study was to examine the impact of mineral feeder design on visitations and intake. In a crossover experimental design, beef cattle operations (n = 5) were randomly assigned to treatment sequence (lid status) and each evaluation period occurred for 5 – 7 days. Browning game trail cameras (Prometheus Group LLC, Birmingham, AL) were used to record time lapse pictures at 2-minute intervals from sunrise to sunset. Time was categorized as morning (≤10:00), mid-day (10:01 – 14:00), afternoon (14:01 – 18:00) and evening (>18:00). Activity was categorized as eating mineral, standing, lying or other within 0.5 m of feeder. Effects of farm, treatment, and time were analyzed using the GENMOD procedures of SAS 9.4 and mineral intake data were analyzed using PROC GLM. There were significant effects of farm (P < 0.001), treatment (P < 0.007), time (P < 0.001), and the treatment by time interaction (P < 0.001) for the numbers of cows and calves eating. Different herd sizes likely contributed to the significance of farm. Data were further analyzed using PROC FREQ. Of the animals eating, more cows and calves were observed eating with the lid removed (59.1% and 61.7%, respectively). However, average mineral disappearance did not differ (P = 0.57) by treatment (50.4 kg vs. 42.0 kg). Regardless of treatment, more cows were observed eating during the morning and afternoon (35% and 34.8%, respectively) than in the evening (10.3%). Similarly, more calves were categorized as eating in the morning and afternoon (29.3% and 41.3%, respectively) than in the evening (14.1%). These preliminary results indicate that feeder design may impact visitation of cows and calves but not average mineral disappearance.